Regulatory framework of the Strategic doctrine of the Kazakhstan machine building in order to ensure the development of transport and agrotechnical plants - Sarsembayev, M.A.; Karazhan, B.S.; Yelegen, A.E. (Bulletin of the Karaganda University “Law Series”, 2023)
This article presents a general analysis of the Strategic Doctrine of the creation of high-tech engineering with a section of transport and agricultural machinery from 2020 to 2040, as an act of “soft” law. The new Kazakh laws and international conventions that will be adopted in the medium and long term are considered in detail and analytically. The authors applied the methods of logical analysis, comparative legal analysis, the method of scientific forecasting in relation to future Kazakh laws, regulatory legal acts, international conventions. The regulatory framework, which forms one of the foundations of the Strategic Doctrine, is divided into the future legislative framework for the automotive industry, railway engineering, agricultural engineering and the norms of existing and new international conventions on digitalization, automation, robotization of the production of automobile, railway, agricultural machinery plants